Pengembangan Kompetensi Membaca Cepat Melalui Teknik Gaya ”SAVI” Dalam Pembelajaran Bahasa Inggris Di Kelas X SMA Negeri 3 Pandeglang - Engkos Kosasih (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
This research departs from the phenomenon that appears during initial reflection. The results of the competency tests conducted on class X.1 students of State High School 3 of Pandeglang - Banten, after participating in speed reading learning, showed that of the 22 students only 53.6% who were able to fulfill the demands of the basic competency indicators that were targeted for learning. Starting from these problems, it needs to be followed up by applying SAVI style techniques in speed reading learning. The research method used is descriptive method and research design using a classroom action research model designed in three cycles. The results of this study show that the development of speed reading competencies using SAVI style techniques could improve student’s learning activities and outcomes. Changes in the increase in student activity during the learning process from cycle 1 to cycle 2 averaged 1.86, while the average from cycle 2 to cycle is 3 1.64. Student learning outcomes from the average value of cycle 1 to cycle 2 is 7.41, while the average of cycle 2 to cycle 3 is 3.42.